Praktik Jual Beli Motor Dengan Sistem Inden di Dealer Yamaha Surya Inti Putra Pekalongan dalam Analisis Teori Ba’i As-Salam - Alim, Fikri; Khasanah, Karimatul (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2022)
This study examines the reasons for the dely in motorcycles delivery and how to analyze the Ba'i As-Salam theory on the practice of buying and selling motorbikes with a pivot system at the Yamaha Surya Inti Putra dealer in Pekalongan. Indent system if in Islamic law can be equated with buying and selling greetings. However, in the motorcycle pivot system that occurs at the Yamaha Surya Inti Putra Pekalongan dealer, the motorcycle is often not in accordance with the agreement promised by the dealer because in general the motorcycle arrives more than the agreed time, when the goods ordered do not match the agreed time. So based on the Ba'i As-Salam theory, it is contrary to one of the legal conditions in buying and selling, where the goods ordered must have clarity when it arrives. This research used field research with a qualitative approach. Research results show that the factor of delay in motorbike delivery, it was caused by production capacity, unit allocation, and certain specifications. The terms of salam that have not been fulfilled by dealers in the practice of buying and selling salam, namely the promised time for delivery of goods because the pivot system does not provide certainty. The reason for the time delay experienced by the Yamaha Surya Inti Pura Pekalongan dealer is included in the category of reasons allowed by sharia because there was no deliberate factor on the part of the dealer.